Fertilizer and residue quality effects on organic matter stabilization in soil aggregates - Fonte, Steven J.; Yeboah, E.; Ofori, P; Quansah, GW; Vanlauwe, Bernard; Six, Johan (2009)
This study examined the influence of organic residue quality and N fertilizer on aggregate-associated SOM in maize cropping systems of southern Ghana. Six residue treatments of differing quality (Crotalaria juncea, Leucaena leucocephala, maize stover, sawdust, cattle manure and a control with no residues added) were applied at 4 Mg C ha-1 yr-1 both with and without fertilizer N additions (120 kg N ha-1 season-1). Soils (0-15cm) were sampled three years after study implementation and wet sieved into four aggregate size classes (8000–2000, 2000– 250, 250–53, and <53 ?m). Small macroaggregates (2000–250 ?m) were further separated into coarse particulate organic matter (>250 ?m), microaggregates within macroaggregates (53-250 ?m), and macroaggregate occluded silt and clay (<53 ?m). N fertilizer additions reduced aggregate stability as was evident from a 40% increase in the weight of the silt and clay fraction (P= 0.014) as well as a decrease in microaggregates across all residue types (P = 0.019). Fertilizer similarly affected C and N storage within these aggregate fractions, while effects of residue quality were largely insignificant. Our results suggest that fertilizer effects on soil aggregation may have important implications for long-term SOM dynamics.